Writing strategies of Chinese EFL senior high school students / He Xiao - He, Xiao (2016)
It has been stated in a number of studies (Nooreiny & Mazlin, 2013; Roya Khoii, 2011; Tangpermpoon, 2008) that English as a Foreign Language (EFL) or English as a Second Language (ESL) students faced difficulties when writing in English. Efficient writing strategies play an important role in enabling students to achieve their English writing success. The purposes of this study are to investigate the writing strategies employed by Chinese EFL senior high school students, identify the difference between proficient and less proficient students on their use of writing strategies in English and explore some possible reasons of using certain writing strategies. This study employed a mixed method approach by using a questionnaire, recall protocols and post-writing interviews. Initial findings reveal that the learners use more strategies at the while-writing stage as compared to strategies at the prewriting and revising stages. The findings also highlight that there is a significant difference between proficient and less proficient learners on the use of some writing strategies. In addition, EFL learners are mainly influenced by exam-oriented writing experience, attitude, writing difficulties, teaching approach and lack of confidence. The findings of this study could shed better understanding on some popular writing strategies used by these EFL learners. It also assists teachers and educators to develop better teaching methods in guiding students to be better equipped with efficient writing strategies.